The Bantam microRNA Is Associated with Drosophila Fragile X Mental Retardation Protein and Regulates the Fate of Germline Stem Cells - Yang, Yingyue (Public Library of Science, 2009)
Fragile X syndrome, a common form of inherited mental retardation, is caused by the loss of fragile X mental retardation protein (FMRP). We have previously demonstrated that dFmr1, the Drosophila ortholog of the fragile X mental retardation 1 gene, plays a role in the proper maintenance of germline stem cells in Drosophila ovary; however, the molecular mechanism behind this remains elusive. In this study, we used an immunoprecipitation assay to reveal that specific microRNAs (miRNAs), particularly the bantam miRNA (bantam), are physically associated with dFmrp in ovary. We show that, like dFmr1, bantam is not only required for repressing primordial germ cell differentiation, it also functions as an extrinsic factor for germline stem cell maintenance. Furthermore, we find that bantam genetically interacts with dFmr1 to regulate the fate of germline stem cells. Collectively, our results support the notion that the FMRP-mediated translation pathway functions through specific miRNAs to control stem cell regulation.